EFL UNIVERSITY STUDENTS EMPLOYED A CRITERIA OF HEDGES DURING THEIR SPEAKING CLASS WITHIN THE ACADEMIC SETTING - Imran Trista Udin; Zulkhaeriyah Zulkhaeriyah; Fiviyanti Hasim (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Communication becomes an essential aspect in language classroom because it bridges the meaning of a person’s ideas. Therefore, as foreign language learners, the students have to have a good understanding at how to interact effectively with other students. Regarding to this, the researcher considered it is crucial to investigate English Foreign Language (EFL) university students’ ways in communication during their speaking class which includes hedges. The objectives of the research was to find out the types of hedges employed by EFL university students during their speaking class within the academic setting. This study was conducted at Politeknik LP3I Makassar and it was focused on the students in the first semesters in subject Basic Speaking with the total participants were 23 students of one class. The method used was descriptive qualitative method. There were 3 recordings based on the students’ interactions in the classroom. The theory from Riekkinen and Svarova (2009) was used to analyze the data gain. After transcribing and analyzing the data, the results showed that the students in EFL speaking class utilized some types of hedges. The hedges used involves personal evaluation, expression of limitation, expression of hesitation, and the combine hedges. Besides, the students employ hedges for some reasons.